2019
DOI: 10.3389/fphar.2019.00797
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic Acid is a Multi-Target Inhibitor of Key Enzymes in Pro-Inflammatory Lipid Mediator Biosynthesis

Abstract: Introduction: Lipid mediators (LMs) comprise bioactive metabolites of polyunsaturated fatty acids, including pro-inflammatory prostaglandins (PGs), thromboxanes (TXs), and leukotrienes (LTs), as well as specialized pro-resolving mediators (SPMs). They are essentially biosynthesized via cyclooxygenase (COX) and lipoxygenase (LO) pathways in complex networks and regulate the progression as well as the resolution of inflammatory disorders including inflammation-triggered cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…should have multitarget activity (Figure 2a-f), and this was verified experimentally with IC 50 values shown of 385, 674, and 46 nM, respectively (Xu et al, 2019). Similarly, the well-known SUMOylation inhibitor, ginkgolic acid, has been identified as a potential hit in pharmacophore-based virtual screening for inhibitors of microsomal prostaglandin E synthase-1 (mPGES-1) and 5-lipoxygenase (5-LO) (Gerstmeier et al, 2019). The docking model supports the molecular interaction of ginkgolic acid with mPGES-1 and 5-LO and provides specific binding sites (Figure 2g,h), correlating with associated IC 50 values of 0.7 and 0.2 μM, respectively (Fukuda et al, 2009).…”
Section: Flexible Dockingmentioning
confidence: 55%
See 1 more Smart Citation
“…should have multitarget activity (Figure 2a-f), and this was verified experimentally with IC 50 values shown of 385, 674, and 46 nM, respectively (Xu et al, 2019). Similarly, the well-known SUMOylation inhibitor, ginkgolic acid, has been identified as a potential hit in pharmacophore-based virtual screening for inhibitors of microsomal prostaglandin E synthase-1 (mPGES-1) and 5-lipoxygenase (5-LO) (Gerstmeier et al, 2019). The docking model supports the molecular interaction of ginkgolic acid with mPGES-1 and 5-LO and provides specific binding sites (Figure 2g,h), correlating with associated IC 50 values of 0.7 and 0.2 μM, respectively (Fukuda et al, 2009).…”
Section: Flexible Dockingmentioning
confidence: 55%
“…Ginkgolic acid fitted into the binding site of mPGES-1 (g) and 5-LO (h) using GOLD software having scores 74.53 and 68.9, respectively. Images in panels (a)-(e) were adapted from (Xu et al, 2019) with permission from Elsevier, while (g) and (h) were adapted from Gerstmeier et al (2019) with permission under a Creative Commons Attribution License (CC BY). EGFR, epidermal growth factor receptor; mPGES, microsomal prostaglandin E synthase; PDGFR, platelet-derived growth factor receptor; VEGFR, vascular endothelial growth factor receptor T A B L E 4 A list of popular force-fields used in molecular dynamics (MD) simulations…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…In addition, our experiment showed that after further treatment of the aqueous methanolic extract with hexane, the level of ginkgolic acid was reduced from 19 ppm to 4 ppm with minor changes in the concentrations of other bioactive constituents. However, the pharmacological properties of ginkgolic acids family are not limited to those mentioned above [29] and undoubtedly deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of these natural products are that they mostly function in the micromolar range and that they do not singly target SUMOylation. Ginkgolic acid is known to target proinflammatory molecules like prostaglandins and leukotrienes [69], and tannic acid can also induce cancer cell death via activation of apoptosis rather than via inhibition of cell cycle progression, as expected for a SUMOylation inhibitor [68]. Trends in Cancer…”
Section: Sae1/uba2mentioning
confidence: 99%